EFFECT OF SALINITY AND GROWTH MEDIUM ON Symbiodinium sp. ISOLATED FROM GIANT CLAM - Panggabean, Maria Goretti Lily; Hutagalung, Rory A.; Ayu, Eveline (Marine Research in Indonesia, 2009)
An experiment on isolate Symbiodinium sp. from Hippopus hippopus was carried out to determine growth medium and optimum salinity for in vitro culture of the symbiont. The split-plot factorial design with two factors was applied with 3 replications. The first factor was medium with 2 levels, namely f/2 and modified GPM. The second factor was salinity with five levels i.e. 20, 25, 30, 35 and 40 PSU. All treatments were incubated under continuous light (2600 lux) and 25Â°C. The maximum growth was reached at day 16 and there was significant interaction (p<0.05) between medium and salinity. The maximum density (64.8 x 104cell/ml) was found in media f/2 and salinity 35 PSU.